2022
DOI: 10.1101/2022.03.10.483655
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IPMK modulates insulin-mediated suppression of hepatic glucose production

Abstract: Hepatic glucose production is crucial for the maintenance of normal glucose homeostasis. Although hepatic insulin resistance contributes to excessive glucose production, its mechanism is not well understood. Here, we show that inositol polyphosphate multikinase (IPMK), a key enzyme in inositol polyphosphate biosynthesis, plays a role in regulating hepatic insulin signaling and gluconeogenesis both in vitro and in vivo. IPMK-deficient hepatocytes exhibit decreased insulin-induced activation of Akt-FoxO1 signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Note that a full list of the articles supported through this center is included within the reference section. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Figure 2 summarizes the center's key accomplishments.…”
Section: Obesity Sfrns : Goals and Resultsmentioning
confidence: 99%
“…Note that a full list of the articles supported through this center is included within the reference section. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Figure 2 summarizes the center's key accomplishments.…”
Section: Obesity Sfrns : Goals and Resultsmentioning
confidence: 99%
“…Overexpression of kinase-dead insulin receptor (IR) or IGF-1 receptor (IGF1R) in muscle led to glucose intolerance, high levels of circulating triglyceride, and insulin resistance in mice [49,50]. Our previous studies have shown that the deletion of IPMK reduced the activity of insulin signaling in hepatocytes and exacerbated high fat-induced insulin resistance in mice [35,51]. Consistent with these findings, the depletion of IPMK in primary myocytes showed reduced AKT activation in response to insulin, and IPMK-MKO mice developed glucose intolerance, similar to findings in mice with overexpression of kinase-dead insulin receptor (IR) or IGF-1 receptor (IGF1R).…”
Section: Discussionmentioning
confidence: 99%
“…To generate adipocytespecific Ipmk knockout mice, Ipmk-floxed mice were mated with MLC-Cre transgenic mice (a generous gift from Dr. Se-Jin Lee, University of Connecticut) (MKO). Ipmk-floxed mice were developed, as described previously [35] and backcrossed with C57BL/6J wildtype for at least five generations. All mice were maintained in a 12:12-h light-dark cycle with free access to regular chow (4.5% fat, 49.9% carbohydrate, 23.4% protein; 4 kcal/g, LabDiet, Richmond, IN) and water in a specific pathogen-free facility in the Johns Hopkins University.…”
Section: Methodsmentioning
confidence: 99%
“…This defect could be rescued by the ectopic expression of IPMK or by the pharmacological activation of AKT with the agonist SC79 in hepatocyte primary cell culture. Consequently, mice lacking liver IPMK showed symptoms of hepatic insulin resistance, including reduced glycogen storage and increased gluconeogenesis in the presence of insulin, and the tendency to gain more weight than their wildtype litter mates on a high fat diet [ 46 ]. While this study shows that IPMK contributes to AKT activation in vivo, the InsP6 kinases have been found to attenuate insulin signaling in two distinct ways: by promoting insulin release and by attenuating AKT activity.…”
Section: The Inositol Phosphate Systemmentioning
confidence: 99%
“…Inositol phosphate signaling is an integral part of energy homeostasis and contributes to cellular energy not only by regulating growth factor signaling, nutrient uptake, and metabolic signaling as previously discussed, but through metabolic programming in unexpected ways. Numerous reports indicate that disrupting inositol phosphate synthesis impacts metabolic functions in unicellular and multicellular organisms, with effects ranging from enhanced glycolysis and gluconeogenesis to lipid synthesis, to changes in mitochondrial function, with severity dependent on cell type and changes in the InsP code [ 46 , 99 , 100 , 101 , 102 ]. For example, the genetic deletion of Kcs1 (IP6K1) in S. cerevisiae increased cellular ATP 3-fold and resulted in a highly glycolytic Warburg phenotype.…”
Section: The Inositol Phosphate Systemmentioning
confidence: 99%